Strengthening Village Anti-Corruption Governance: Strategies, Challenges, and Policy Implementation in Swastika Buana Village, Indonesia - Putra Pratama, M Aviv Adhitya; Jefri, J.; Budiman, B.; Afrilia, Merina; Syahid, Imam (Manunggal Halim Jaya, 2025)
This research aims to analyse the strengthening of anti-corruption-based village governance through a regulative approach and the role of social institutions in Swastika Buana Village. In the context of the increasing urgency of transparency and accountability at the village government level, this research focuses on how local legal instruments can build institutional integrity. The method is a descriptive qualitative approach with data collection techniques through in-depth interviews, participatory observation, and document analysis. The results showed that the village has established several Village Regulations (Perdes), Village Head Decrees, and SOPs that systematically regulate village financial governance, including the planning, implementation, administration, and accountability of the APBDes. In addition, a periodic and structured mechanism for evaluating the performance of village officials has been implemented, as well as regulations regarding the control of gratuities, bribes, and conflicts of interest. The process of procuring goods and services has also followed formal standards through cooperation agreements with providers to apply the principles of legality and accountability. The active participation of the community and the role of local social institutions are proven to strengthen the effectiveness of the regulation's implementation and encourage more open and anti-corruption government practices. This research provides theoretical implications for the development of local institution-based governance, as well as managerial recommendations related to increasing the capacity of the apparatus, digitising the village system, and internalising public ethical values.